2021
DOI: 10.1021/acs.joc.1c00051
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Preference of 2′-Fluoro-Substituted Acetophenone Derivatives Revealed by Through-Space 1H–19F and 13C–19F Spin–Spin Couplings

Abstract: The conformational properties of 2′-fluoro-substituted acetophenone derivatives were elucidated based on H α –F and C α –F through-space spin–spin couplings (TS-couplings), which occur between two atoms constrained at a distance smaller than the sum of their van der Waals radii. This study revealed that 2′-fluoro-substituted acetophenone derivatives in solutions form exclusively s - trans conformers by analyzing their N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…It is worth mentioning that the coupling constants ( 5 J HF = 1.4–1.8 Hz) (Table ) associated with through- space coupling in compounds 1 and 2 are smaller than those in 2′-fluoro-substituted acetophenones ( 5 J HF = 3.2–5.0 Hz), as reported in our previous study (Figure ). The TBC constants ( 5 J HF ) of most compounds are generally less than 1 Hz, which is similar in magnitude to those observed for compounds 1 and 2 . However, it should be noted that, although 1 H– 19 F coupling was observed in one of the diastereotopic protons (H 6a ′ and H 4a ′ in compounds 1 and 2 , respectively), no such couplings were observed for other diastereotopic protons (H 6b in compound 1 and H 4b in compound 2 ), which are both five bonds apart from the F in CF 3 group.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…It is worth mentioning that the coupling constants ( 5 J HF = 1.4–1.8 Hz) (Table ) associated with through- space coupling in compounds 1 and 2 are smaller than those in 2′-fluoro-substituted acetophenones ( 5 J HF = 3.2–5.0 Hz), as reported in our previous study (Figure ). The TBC constants ( 5 J HF ) of most compounds are generally less than 1 Hz, which is similar in magnitude to those observed for compounds 1 and 2 . However, it should be noted that, although 1 H– 19 F coupling was observed in one of the diastereotopic protons (H 6a ′ and H 4a ′ in compounds 1 and 2 , respectively), no such couplings were observed for other diastereotopic protons (H 6b in compound 1 and H 4b in compound 2 ), which are both five bonds apart from the F in CF 3 group.…”
Section: Resultssupporting
confidence: 73%
“…Two nuclei, such as 19 F/ 19 F, 19 F/ 1 H, and 19 F/ 13 C, can exchange spin information when in van der Waals contact through space, regardless of the number of chemical bonds separating them. 4 In the course of our studies on the syntheses of bioactive compounds, 5 we accidentally observed TSCs with significant magnitudes ( 5 J HF = 3.2−5.0 Hz) in the 1 H NMR spectra of 2′fluoro-substituted acetophenone derivatives. These TSCs revealed that 2′-fluoro-substituted acetophenone derivatives in solution exclusively form s-trans conformers (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Heteronuclear nOe (nuclear Overhauser effect) was observed between H8 and fluorine atom, indicating spatial proximity between these nuclei and bringing to the discussion the possibility of a through-space transmission pathway via intramolecular H-bond ( 1h J FH8 ), instead of a solely through bond transmission pathway ( 4 J FH8 ). Recently, studies conducted by Takahashi and coworkers 48,49 and by Suryaprakash and coworkers 50–53 have also employed 1 H– 19 F HOESY experiment to confirm the presence of intramolecular H-bond. What is intriguing about these compounds is the presence of this kind of interaction in a polar solvent such as DMSO- d 6 , once it is expected that the solvent molecules would prefer to interact with the solute, thus breaking the intramolecular H-bond.…”
Section: Resultsmentioning
confidence: 99%